Sky's the Limit: The Operations, Renovations and Implications of a Montréal Gay Bar - Allan, James (Université McGill, 1997)
"A burgeoning mega-club in the heart of Montreal's gay village, Sky embodies many forces active in gay club cultures and villages across North America at the end of the twentieth century. This project documents the daily operations of Sky–as a complex architectural site, a complicated set of managerial practices, and a popular space in Montreal's Village–and outlines the theoretical implications of such an establishment for both the gay community and for club culture more generally. A large entertainment complex currently undergoing a major expansion, Sky cannot be theorized as either a wholly oppressive or completely liberatory development. Although Sky presents some of the advantages of a mega-club for the gay community–increased diversity, accessibility and community–it also highlights the disadvantages in the development of such establishments: concentration of ownership, the removal of a gay presence from city streets, and the promotion of certain gay identities and cultures over others."

De l’oreille au cœur. Naissance du chant religieux en langues amérindiennes dans les missions de Nouvelle-France, 1600-1650 - Dubois, Paul-André (Septentrion, 1997)

Naissance du cantique en langue vernaculaire dans les missions de Nouvelle-France et conquête des langues amérindiennes : une relation - Dubois, Paul-André (Recherches amérindiennes au Québec, 1997)

Céline - Germain, Georges-Hébert (Éditions Club Québec Loisirs, 1997)
Voici le portrait d'une femme libre, autonome, amoureuse, physiquement et mentalement saine et souple. Céline Dion est portée par une grande ambition, qui n'est pas celle des autres mais la sienne propre, et par ses rêves à elle, que son imprésario, l'homme de sa vie, René Angélil, l'aide à réaliser. L'histoire racontée ici est faite de multiples conquêtes, certaines longues et ardues, d'autres faciles ou imprévues. Certaines de ces conquêtes sont intimes, d'autres sont hautement spectaculaires et médiatisées.

Répertoire des œuvres des compositrices du Québec au XXe siècle - Labelle, Nicole (Centre de recherche en civilisation canadienne-française, 1997)

Emma Albani. La diva, la vedette mondiale - Labrèche-Larouche, Michelle (XYZ, 1997)
La vie de la célèbre cantatrice canadienne-française qui, au XIXe siècle, conquit l’Europe et l’Amérique et fut l’amie de la reine Victoria et de célèbres compositeurs tels Liszt et Brahms.

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation m the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.

Vicissitudes - Maidanik, Victoria (Université McGill, 1997)
Vicissitudes is a composition for orchestra with a duration of approximately 13$ sp prime$ 30$ sp{ prime prime}$. The main idea of the piece, the subdivision of the orchestra into small soloistic groups along with larger ensembles, was inspired by the principles of one of the Baroque forms, namely the Concerto Grosso.

À la manière des préludes non mesurés - Panneton, Isabelle (Circuit : musiques contemporaines, 1997)
Faisant état de l’influence sur elle du répertoire baroque, la compositrice montre quel rôle de modèle ont joué pour elle les préludes non mesurés de Rameau et Couperin, notamment dans son oeuvre Trait, Écart, Réparties. Elle en indique ensuite les prolongements dans quelques autres pièces.

La critique féministe étatsunienne en musique : pertinence en milieu francophone Québécois - Sabourin, Carmen (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)

Selected intermediate to early-advanced works for piano solo by Violet Balestreri Archer: An analysis for teaching and performance - Soo, Rosalyn Wai-yan (Université d'Oklahoma, 1997)
The ensuing four chapters present analyses of the selected works. The discussion of each composition begins with a brief introduction about its background, stylistic traits, and influences. A structural analysis follows, addressing traditional musical parameters and how they are manipulated by Archer's contemporary style. Analytical elements include the investigation of main sections, tonal areas, character, compositional devices, and style. An additional aesthetic goal of the analysis is to consider the musical elements of the works with regard to a listener's possible perceptions.